Leadership Dynamics in Islamic-Based Schools: A Systematic Review of Southeast Asia (2015–2025) - Eka Rizki Amalia (At-tadzkir: Islamic Education Journal, 2026)
This study presents a systematic literature review (SLR) of leadership styles in Islamic-based schools across Southeast Asia by synthesizing 37 peer-reviewed studies published between 2015 and 2025. Guided by PRISMA protocols and Braun and Clarke’s thematic analysis, the review identifies three dominant models of leadership: servant, instructional, and transformational, and highlights the growing emergence of hybrid adaptations. Servant leadership predominates in community-driven schools where moral legitimacy and social trust underpin leadership authority. Instructional leadership is most visible in structured systems that emphasize accountability and curriculum supervision, while transformational leadership arises in reform-oriented schools that integrate faith with innovation. Collectively, these styles intersect to form a faith-integrated leadership paradigm, blending ethical service, pedagogical rigor, and visionary reform. The study advances leadership theory by contextualizing classical Western frameworks within Islamic epistemological principles such as amanah, shura, and taqwa. Empirically, it offers cross-country insight into how institutional and cultural ecologies shape leadership expression. The findings have practical implications for leadership training and policy, suggesting the need for culturally responsive, Islamically grounded leadership frameworks that enhance teacher motivation, school accountability, and institutional development across Southeast Asia.